Bei Dao e a Era Glacial: Tradução e Comentários do poema “A Resposta” (回答) - Menezes Júnior, Antonio José Bezerra de (TradTerm, 2011)
This paper aims to translate and examine the poem "The Answer" by the poet Bei Dao, one of the leading names in contemporary Chinese poetry, especially the post-Cultural Revolution poetry.